Clinical and neuroimaging criteria to improve the workflow in transfers for endovascular treatment evaluation. Issue 9 (December 2020) - Requena, Manuel; Olivé-Gadea, Marta; Boned, Sandra; Ramos, Anna; Cardona, Pere; Urra, Xabier; Serena, Joaquín; Silva, Yolanda; Purroy, Francisco; Ustrell, Xavier; Abilleira, Sonia; Tomasello, Alejandro; et al.
Background: Transfer protocols from primary to comprehensive stroke centers are crucial for endovascular treatment success. Aim: To evaluate clinical and neuroimaging data of transferred patients and their likelihood of presenting a large infarct core at comprehensive stroke center arrival. Methods: Retrospective analysis of population-based mandatory prospective registry of acute stroke patients evaluated for endovascular treatment. Consecutive patients evaluated at primary stroke center with suspected large vessel occlusion and PSC-ASPECTS ≥ 6 transferred to a comprehensive stroke center were included. PSC and CSC-ASPECTS, time-metrics, and clinical data were analyzed. Results: During 28 months, 1185 endovascular treatment candidates were transferred from PC to comprehensive stroke center in our public stroke network, 477 had an anterior circulation syndrome and available neuroimaging information and were included. Median baseline NIHSS was 13 (8–19). On arrival to comprehensive stroke center, large vessel occlusion was confirmed in 60.2% patients, and 41.2% received endovascular treatment. Median interfacility ASPECTS decay was 1 (0–2) after a median of 150.7 (SD 101) min between both CT-acquisitions. A logistic regression analysis adjusted by age, time from symptoms to PC-CT, and time from PC-CT to CSC-CT showed that only a baseline NIHSS and PSC-ASPECTS independently predicted a CSC-ASPECTS < 6. ROC curves identified baseline NIHSS ≥ 16 and PSC-ASPECTS ≤ 7 as the best cut-off points. The rate of CSC-ASPECTS < 6 increased from 7% to 57% among patients with NIHSS ≥ 16 and PSC-ASPECS ≤ 7. Conclusion: After a median transfer time >2 h, only 11.9% showed ASPECTS < 6 at the comprehensive stroke center. Activation of endovascular treatment teams should not require confirming neuroimaging on arrival and repeating neuroimaging at comprehensive stroke center should only be performed in selected cases.